A 12 years old boy with carcinoma rectum - Debnath, CR; Debnath, MR; Gafur, MA; Huq, MH (Mymensingh Medical Journal, 2010)
Mymensingh Med J. 2010 Jan;19(1):116-118. The abstract of this article is available on the PubMed website